Automatic Control System for Dissolved Oxygen in Vanname Shrimp Pond Water - Amalia Nur Hikmah; Peni Handayani; Trisno Yuwono Putro (Politeknik Negeri Bandung, 2019)
Dissolved oxygen is an important parameter for the life of vanname shrimp ponds that are environmentally sensitive. The control system of dissolved oxygen is still done manually by pond farmers who have to go directly to the location of the pond to measure it. This was felt by pond farmers as being less than optimal and effective in maintaining dissolved oxygen requirements for vanname shrimp so that farmers often lose money. This project aims to make a system of controlling dissolved oxygen in water of vanname shrimp ponds automatically. The system has been realized 100% with the percentage of the calibration measurement results reading 99,45% dissolved oxygen and controlling the appropriate dissolved oxygen level reaching 100%. This system is expected to optimize the control of dissolved oxygen in vanname shrimp pond water so that the production and quality of shrimp increases.